2021
DOI: 10.1590/0004-282x-anp-2020-0041
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety of azathioprine for treatment of neuromyelitis optica spectrum disorders

Abstract: Background: Azathioprine is a common first-line therapy for neuromyelitis optica spectrum disorder (NMOSD). Objective: The aim of this study was to determine whether long-term treatment (>10 years) with azathioprine is safe in NMOSD. Methods: We conducted a retrospective medical record review of all patients at the School of Medicine of the University of São Paulo (São Paulo, Brazil) who fulfilled the 2015 international consensus diagnostic criteria for NMOSD and were treated with azathioprine for at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…A retrospective study with the first-line therapy of NMOSD confirmed MMF as the first-line therapeutic option and added that AZA was worth considering if the side effects were tolerable [ 50 ]. Studies have pointed out that the long-term use of AZA or MMF increases the risk of hematologic malignancies [ 51 , 52 ]. Note-worthily, such threats may not spring up in short-term observations and thus could have been severely underestimated as potential side effects.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study with the first-line therapy of NMOSD confirmed MMF as the first-line therapeutic option and added that AZA was worth considering if the side effects were tolerable [ 50 ]. Studies have pointed out that the long-term use of AZA or MMF increases the risk of hematologic malignancies [ 51 , 52 ]. Note-worthily, such threats may not spring up in short-term observations and thus could have been severely underestimated as potential side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Azathioprine is a prodrug of 6-mercaptopurine and an immunosuppressive antimetabolite. There are single centre reports on azathioprine in NMOSD with up to 103 patients and two meta-analyses covering 977 and 1016 patients [8][9][10][11][12]. Higher case numbers on adverse events (AEs) have been derived from other indications, in particular, inflammatory bowel disease, rheumatoid arthritis (RA), and the early days of kidney transplantation [13][14][15].…”
Section: Azathioprinementioning
confidence: 99%
“…However, the descriptions of serious infections in NMOSD patients under azathioprine treatment are rare. Elsone et al reported three cases of respiratory infections (out of 103 patients, corresponding to 2.9%), Gomes et al reported on one patient with tuberculosis (out of 19, 5.3%) [9,11]. In inflammatory bowel disease, the reported infection rates range from 2% to 42% [13].…”
Section: Azathioprinementioning
confidence: 99%
See 1 more Smart Citation